Determinantes del precio de la vivienda en el Distrito Metropolitano de Quito periodo 2010-2018. - Haro Benítez, Luis Enrique (2021)
This research identifies the main determinants of the new housing price in the Distrito Metropolitano de Quito during 2010-2018. For this purpose, the respective theoretical analysis was carried out, with the help of the INEC database, the variables were classified and ordered. Then an econometric model of Weighted Least Squares was proposed for the contribution in the reduction of residuals, achieving a better fit in the investigation. In this way, it was possible to verify the importance and hierarchy of each one, as a result; The model revealed the most representative variables with a 95% adjustment where each variable causes the dependent (house price) with almost 99% adjustment, which were: areas for green spaces, structure, number of rooms per dwelling, construction area, land area in square meters, number of floors.